INCREASING STUDENTS VOCABULARY OF GRADE VIII AT SMPN 1 GALANG THROUGH WORD CLAPPING GAME - Reza Aprilieah (Jurnal Madako Education, 2018)
This research is based on the problem of the students were didn’t know the meaning of the word of Eight Grade,because the students lack vocabulary.This Research is aimed to application of word clapping game on teaching vocabulary and furthermore to know the achievement or not after teaching learning through word clapping game.Itconducted the studied used pre-experimental research it’s mean that just focused on one class from the four parallel class and it applied purposive sampling. The instruments of the research is pre-test and post-test. Furthermore the students mean score in post-test 79,18 was increase while mean score pre-test 44,86.The data were analyzed by using SPSS program. The researcher concluded that was through word clapping game can increasing the students vocabulary. Key word : Increase, Vocabulary, Word Clapping Game